The implementation of un security council resolutions and human rights protection in the EU legal order - Eren, Esra Yılmaz (My University, 2010)
ted Nations Security Council Resolutions, Economic Sanctions, European Court of Justice restrictive measures Cases, Human Rights protection.

THE IMPLEMENTATION OF UN SECURITY COUNCIL RESOLUTIONS AND HUMAN RIGHTS PROTECTION IN THE EU LEGAL ORDER In the last decade, economic sanctions have become a major instrumentality of the UN Security Council in the struggle against terrorism. The implementation of those restrictive measures within the EU has brought many legal conflicts along with it. In this context, the thesis turns to a discussion of the UN's sanctions regime and the issues raised in recent litigation in the European Courts – Kadi and Yusuf- surrounding implementation of that regime in the European Union and its Member States. The competence of the Union to implement economic sanctions, the place of the UNSC Resolutions within the Community hierarchy of norms has been analyzed. Furthermore, the study describes the economic sanctions regime and the various judicial remedies across multiple levels of law- International, European and national- that the accused individuals may apply for remedy. In conclusion, it is supported that, since the affected individuals who have been subject to economic sanctions due to being in the “Terrorist watch lists” of the UNSC, have no locus standi before the International law, European Courts ought to provide judicial remedy for them and the UNSC Resolutions should be subject to judicial review. rleşmiş Milletler Güvenlik Konseyi Kararları, Kısıtlayıcı Önlemler, Avrupa Adalet Divanı ekonomik yaptırım davaları, İnsan Hakları koruması. ÖZET AVRUPA BİRLİĞİ HUKUKUNDA BİRLEŞMİŞ MİLLETLER GÜVENLİK KONSEYİ KARARLARININ UYGULANMASI VE İNSAN HAKLARI KORUMASI Son yıllarda ekonomik yaptırımlar BM Güvenlik Konseyinin teröre karşı savaş konusunda kullandığı önemli bir araç haline gelmiştir. Bu tedbirlerin AB bünyesinde alınan kararlarla uygulanması pek çok hukuki sorunu da beraberinde getirmiştir. Bu bağlamda emsal karar olarak nitelendirilebilecek olan Yusuf ve Kadı davaları esas alınarak, kısıtlayıcı önlemlerin birlik içerisinde uygulanmasının doğurduğu sonuçlar incelenmiştir. Kararlarda tartışıldığı üzere, birliğin ekonomik tedbir uygulama yetkisi, BM Güvenlik Konseyinin AB Hukuku normlar hiyerarşisindeki yeri ele alınmıştır. Bu tezde özellikle ekonomik yaptırımlara maruz kalan bireylerin uluslararası hukuk, Avrupa Hukuku ve yerel hukuk açısından başvurabilecekleri hukuki mekanizmalar araştırılmış, konuya ilişkin emsal kararlara değinilmiştir. Ayrıca, Birleşmiş Milletler Güvenlik Konseyi nezdinde hazırlanan “Terörist İzleme Listeleri”nde adlarının bulunması nedeniyle kısıtlayıcı tedbirlere maruz kalan bireylerin uluslararası hukukta BM güvenlik Konseyi kararlarını dava edebilecekleri bir mekanizma olmaması nedeniyle Adalet Divanı ve AİHM nezdinde korunmaları ve Güvenlik Konseyi kararlarının da yargısal denetime tabi tutulması gerektiği savunulmaktadır.
Keywords: Avrupa Birliği; Avrupa Birliği Hukuku; Birleşmiş Milletler Güvenlik Konseyi Kararları; İnsan Hakları